2018
DOI: 10.1101/409896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro activity of a novel antifungal compound, MYC-053, against clinically significant antifungal-resistant strains of Candida glabrata, Candida auris, Cryptococcus neoformans, and Pneumocystis spp

Abstract: An urgent need exists for new antifungal compounds to treat fungal infections in immunocompromised patients. The aim of the current study was to investigate the potency of a novel antifungal compound, MYC-053, against the emerging yeast and yeast-like pathogens Candida glabrata, Candida auris, Cryptococcus neoformans, and Pneumocystis spp. MYC-053 was equally effective against the susceptible control strains, clinical isolates, and resistant strains, with the minimum inhibitory concentrations (MIC) of 0.125–4.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The pyrimidinedione derivative MYC-053 ( 48 ) showed broad spectrum effects against Candida spp., Cryptococcus spp., and Pneumocystis spp. It had an MIC value of 4 μg/mL against 5 C. auris isolates, and it was also active against several strains resistant to fluconazole and caspofungin 151 .…”
Section: New Targets For the Development Of Anti- C Auris ...mentioning
confidence: 99%
“…The pyrimidinedione derivative MYC-053 ( 48 ) showed broad spectrum effects against Candida spp., Cryptococcus spp., and Pneumocystis spp. It had an MIC value of 4 μg/mL against 5 C. auris isolates, and it was also active against several strains resistant to fluconazole and caspofungin 151 .…”
Section: New Targets For the Development Of Anti- C Auris ...mentioning
confidence: 99%
“…In 2019, Tetz et al described the in vitro activity of a novel compound name 053 ( Figure 13) against clinically significant multidrug resistant strains such as C. C. auris, C. neoformans and Pneumocystis spp. [77,78]. Under their screening con MYC-053 proved to be equally effective against both susceptible control strains, Montoya et al reported that derivatives of the anti-malarial drug mefloquine have broad-spectrum antifungal activity against pathogenic yeasts and molds [80].…”
Section: In Vitro Evaluationmentioning
confidence: 99%
“…CSA steroids as patented by Genberg, Beus and Savage and MYC-053 as reported byTetz. In 2019, Tetz et al described the in vitro activity of a novel compound named MYC-053 (Figure 13) against clinically significant multidrug resistant strains such as C. glabrata, C. auris, C. neoformans and Pneumocystis spp [77,78]…”
mentioning
confidence: 99%
“…Because of this, drug resistance of common fungal pathogens, such as C. neoformans , C. albicans , and A. fumigatus , has become a growing burden on the healthcare system worldwide. Most alarming is the emergence of fungal species, such as C. auris and C. glabrata , that were already resistant to current antifungal agents [ 12 ]. Thus, there is an urgency for the development of novel antifungal drugs with new mechanisms of action to be used alone or in combination with current antifungals.…”
Section: Fungal Infections In Humans and Current Antifungal Drugsmentioning
confidence: 99%